Sharks Past, Present and Future - Nejmeddine Bradai, Mohamed; Enajjar, Samira; Saidi, Bechir (IntechOpen, 2023)
This book presents information on the biology, ecology, taxonomy, and fisheries of sharks. The analysis of data shows that cartilaginous species, including sharks, rays, and chimeras, are by far the most endangered group of marine fish. Sharks are particularly vulnerable to exploitation because of their K-selected life-history strategy. Overfishing, wide use of non-selective fishing practices and habitat degradation are leading to dramatic declines of these species in most marine areas. In general, sharks are not targeted but are caught incidentally. In many fisheries, they are, however, often landed and marketed. Therefore, this book provides recommendations for protecting and managing sharks' stocks. A better understanding of the composition of incidental and targeted catches of sharks by commercial fisheries and biological and ecological parameters are fundamentally important for the conservation of these populations.